A Methodology for Investigating Aerosolization of Nontuberculous Mycobacteria From Contaminated Heater Cooler Devices - Guha, Suvajyoti; Wolloscheck, David; Abdali, Narges; Wentz, Catherine; Gillette, Nicole; Bauer, Kelly A.; Weeks, Jon W. (Frontiers in Water, 2022)
Aerosols inadvertently generated by the bubbling of contaminated water in heater cooler devices (HCDs) have been associated with hundreds of patient infections. These aerosols are typically generated by bubbling within the water tanks of HCDs that subsequently escape from the device leading to contamination of the operating room and potentially infect patients undergoing cardiothoracic surgery. Although these infections are now well reported in literature, very little research has been done to understand the influence of bubbling frequencies, differences in aerosolization across various species of bacteria, sampling methodologies, infectious dose, etc. Here we report on the development of a miniaturized bubbler with a footprint much smaller than HCDs, that will enable academic researchers and HCD developers to investigate these parameters. Using this bubbler, we found that the aerosolization potential of slow growing Mycobacterium chimaera is about one hundred-fold more (p<0.05) compared to rapid growing M. smegmatis for low inoculum concentrations (≤ 106 CFU/mL), underscoring the need for using clinically relevant M. chimaera for evaluating the aerosolization potential of nontuberculous mycobacteria (NTM) from HCDs.